Learners Strategies Used by Non-English Department Students in Learning English: Students’ Perspective - Wahyuningsih, Linda; Huwaidah, Haya Kantina; Maryam, Fitria Fatikha Dewi; Arochman, Taufik (Kajian Bahasa dan Sastra (KABASTRA), 2023)
The learner's strategy in learning a language is one of the things that we must pay attention to, especially in learning a new language such as English. For students of English education who study English, they are usually given specific strategies starting from the classroom to everyday life. However, it is different from a student's non-English department. They must have their own perspective to learn English which they must know and understand for their own benefit. Both the English and non-English departments must have perspectives and strategies that match their criteria. This research aims to prove the presence of the different strategies they used. The method used in this study was descriptive qualitative. The researchers used a questionnaire as their instrument with a total of 32 participants. The finding underlines the two things: the difficulties and the strategies. The difficulties commonly faced by students of non-English department because they realized that English is important but they don’t use English as their everyday life. Thus, it is considered difficult to be practiced. Meanwhile, there were strategic factors used by students both internal factors, self-taught learning using social media, and external factors such as courses. This research gives valuable to the teachers who want to teach their students especially for the learner’s non-English department